Dissimilar CMT joining of aluminum to Ti–Ni–Hf shape memory alloy with Al–Si filler - Huan He; Zhaoxian Liu; Lixin Zhang; Wenzhen Zhao; Ao Fu; Xiaoyang Yi (Journal of Materials Research and Technology, 2023)
The joining of aluminum alloy and Ti–Ni–Hf shape memory dissimilar metals was realized by cold metal transfer (CMT) welding-brazing with an Al-based filler for the first time. The relationship between heat input, microstructures, and joint strength was studied. The joint consisted of three regions: the Al/SMA brazing interface, weld metal zone and Al-weld metal zone. The interfacial intermetallic compound (IMC) with thin strip or needle-like morphology was identified to be TiAl3. An inhomogeneous morphology of the IMC was observed from top to bottom along the brazing interface. The Ti–Ni–Hf SMA adjacent to the interface still presented reversible martensitic transformation. Moreover, the phase transition temperature increased slightly with the increasing of distance from the interface due to the variation in the Ti + Hf/Ni ratio. This meant that the functional properties of Ti–Ni–Hf SMA were not significantly affected by welding. With increasing heat input, the thickness of the IMC increased, and the joint strength decreased. The maximum tensile strength reached 122 MPa when the heat input was 553.6 J/mm. The fracture originated from the interface between the IMC and Ti–Ni–Hf and then propagated along the interface.